Thicket expansion in a vachellia karroo-dominated landscape and its effect on herbaceous communities - Khoza, Marina Rindzani (Rhodes University, Faculty of Science, Botany Department)
Grass and forb species found in savannas are highly diverse, contributing to the structure and function of the savanna system. Where mean annual rainfall is seasonal and high enough to support closed canopy vegetation such as forests or thickets, savannas can exist as an alternative stable state maintained by disturbances such as fire and browsing. Biotic and abiotic processes act on savanna and forest (or thicket) systems maintaining both their tree and herbaceous cover at levels that ensure their persistence in those states. Studies have shown that many semi-arid rangelands in South Africa have undergone a rapid increase in tree cover (of both native and non-native species) over the past several decades. This process of increasing tree cover in semi-arid savannas, termed bush encroachment, results in a biome shift, changing landscapes that were once grasslands with few trees to ones dominated by broad-leaved trees with fewer sun-adapted forbs and grasses. The aim of this study was to investigate the impact of changing woody cover and its associated changes in tree composition, tree canopy structure, light dynamics in the understory and herbaceous community composition on Endwell farm in the Eastern Cape. Canopy cover changes between the years 1949 and 2019 were analysed at 51 sites on the farm and related to historical rainfall patterns. There had been a general increase in tree cover over the past several decades on the farm, and many sites showed a change from open (0-15%) in 1949 to low (1635%), moderate (36-50%) and high (51-100%) canopy cover in 2019. In earlier years most sites had a canopy cover below 50%, and the higher canopy cover values (>65%) occurred in more recent decades. Canopy cover of ~ 50% was found to be rare in each decade. This suggests that ~50% canopy cover maybe a transient, unstable state. The period with the highest rate of canopy cover increase was 2002-2013, and this increase coincided with a high mean annual rainfall 10 years prior to 2002 and a high mean annual rainfall in most years between the 20022013 period. The period between 2002 and 2013 also had the highest number of sites transitioning from lower to higher tree canopy cover classes, indicating that rainfall may have been a factor driving bush encroachment during the past several decades. An increase in canopy cover (a decrease in light transmittance) was accompanied by changes in woody species composition during thicket formation. The low canopy cover (high light transmittance) sites were dominated by Vachellia karroo and Scutia myrtina trees, while high tree cover sites had fewer V. karroo and S. myrtina trees and were rather characterised by an abundance of thicket tree species. Species proportion, NMDS and dendrogram plots indicated that sites with a light transmittance range between 50-100% had similar tree species compositions, different from sites with light transmittances <50%. An increase in tree density was strongly correlated to an increase in canopy cover (from 2019 satellite imagery), density of trees > 3m, maximum height reached by trees, diversity of trees, total canopy volume, total canopy area and leaf area index (LAI), and a decrease in light transmittance. A structural equation model (SEM) was used to explore the relationships between canopy characteristics (maximum canopy area, canopy volume, tree diversity, density of trees, density of trees >3m, individual trees and maximum canopy height), aerial canopy cover in 2019, and light transmittance. The model explained 73% of the variation in light transmittance, mostly via the direct effect of canopy characteristics. Canopy characteristics had a strong influence on both aerial cover in 2019 and directly on light transmittance, but canopy cover in 2019 had a weak influence on light transmittance. The herbaceous layer was rich and dominated by C4 grasses such as Eragrostis plana, Sporobolus fimbriatus, Themeda triandra and Digitaria eriantha) and forbs including Hibiscus aethiopicus, Helichrysum dregeanum, Helichrysum nudifolium and Gerbera viridifolia at low canopy cover sites with high light transmittance. In contrast, high tree cover sites had fewer herbaceous species in general. Grass and forb species characteristic of these sites high canopy cover sites were Panicum maximum, Loudetia flavida, Pellaea viridis and Cyperus spp. Different sites with low light transmittance (<50%) had similar herbaceous species composition. Basal cover, richness, abundance and diversity of herbaceous plants decreased significantly with an increase in tree density, density of trees >3 m, canopy volume, canopy area, canopy cover, LAI, and increased significantly with increasing light transmittance. Most grasses had their highest densities at LAI <0.5, which was estimated to correspond to ~75% light transmittance and ~38% canopy cover and then started to decline thereafter. Herbaceous species basal cover was also highest at LAI <0.5. An SEM model indicated that herbaceous diversity, basal cover and richness responded both to light availability and to the structure of the woody vegetation directly (R2 = 0.53). While the effect of light transmittance on herbaceous communities was strong (0.41), there was little difference between the effect of light transmittance and canopy characteristics (-0.35) on herbaceous communities. Two possible threshold points, relating to two types of transitions in vegetation structure, could be deduced from this study. The first threshold occurred at canopy cover ~ 40% (LAI < ~ 0.5, light transmittance ~ 75%), at which point many of the common herbaceous species, including the dominant C4 grasses, began to decline in abundance while the composition remained characteristic of the savanna state. A canopy cover of less than ~ 40% at a site provides a suitable state for a high abundance of grass and forb species which help maintain an open system by facilitating fires. The second threshold marked a compositional shift between savanna and closed-canopy vegetation states. Savanna species (trees, grasses and forbs) dominated at high light transmittances (>50%) and were significantly reduced at low light transmittances (< 50%), indicating a possible species composition threshold at ~50% light transmittance at which a savanna state switches to a thicket (LAI ~ 1 and canopy cover ~70%). This point indicated the point where there was a significant difference in both tree and herbaceous plant compositions, with a marked reduction in the occurrence of C4 grasses at light transmittance <50%. Fire is supressed when the C4 grass layer is lost, and further thicket encroachment will take place causing complete canopy closure. Land managers in this system should start becoming concerned about a reduction in grass biomass when canopy cover reaches about 40% and would have to reduce tree cover before the threshold of 50% light transmittance (70% canopy cover from aerial photos) is reached to maintain a savanna system.
Keywords: Savanna ecology -- South Africa; Forbs -- South Africa; Grasslands -- South Africa; Herbaceous plants -- South Africa; Vegetation dynamics -- South Africa; Forest canopies -- South Africa